Optimization of extraction process and solvent polarities to enhance the recovery of phytochemical compounds, nutritional content, and biofunctional properties of Mentha longifolia L. extracts - Meryem Tourabi; Khaoula Faiz; Rachid Ezzouggari; Bouchra Louasté; Mohammed Merzouki; Musaab Dauelbait; Mohammed Bourhia; Khalid S. Almaary; Farhan Siddique; Badiaa Lyoussi; Elhoussine Derwich (Bioresources and Bioprocessing)
Abstract The current study attempted to evaluate the influence of three extraction processes such as Soxhlet, ultrasound-assisted extraction (UAE,) and cold maceration on one hand and solvent polarities (ethanol 70%, ethyl acetate, and water) on the other hand, vs. phytoconstituents and biofunctional properties of Mentha longifolia L. Noteworthy, all extracts were examined in terms of their chemical components, phenolic and flavonoid content, antioxidant and antimicrobial potentials. Notably, high-performance liquid chromatography coupled with array detector analysis (HPLC–DAD) showed the existence of many phenolic compounds. Hydro-ethanol extract (ETOH 70% (v/v)) prepared with maceration and Soxhlet process showed the ultimate rate of phenolic compounds coupled with the most powerful antioxidant and antimicrobial capacity. Notably, ETOH extract obtained with UAE showed important nutritional properties, particularly soluble carbohydrate (50.1 ± 0.70 mg/g dry weight), and soluble protein (26.5 ± 0.5 mg/g dry weight), while aqueous extract obtained by use of UAE extraction maximized pigment content. The outcome of this work showed that Soxhlet and maceration extraction processes with many polar solvents are more appropriate for M. longifolia extraction. M. longifolia possesses promising phytochemicals, which can be used in different sectors like food, pharmaceutical, and cosmetic formulations. Graphical Abstract